As interferências subjetivas da língua materna no processo de aquisição da língua francesa : entre a captura e a resistência - Silva, Saulo Albino da (2012)
This dissertation investigates the difficulties regarding the learning process of some students of French language that, despite the fact of being in intermediate and advanced levels of their studies, presented a considerable level of difficult regarding speaking in French. This leads us to made the assumption that such inequality could be attributed to the interference from their mother language and the link that each one of the students had with it, as each time that the students tried to speak in French, they demonstrated levels of hesitation, trying to search for references in the Portuguese language, translating the words they wished to say, in a sort of process of looking for similarities with in their native language. Some of the students were capable of conduct simple speeches and others were not able to assembly complexes sentences.It s important to emphasize that those students seemed to demonstrate interest in learning the French language, fact that sounded contradictory, as if they had the willingness to learn, why there were high levels of difficulties in their learning process? Standing such particularity, using the notion of the unconscious structured as a language form, proposed by Lacan, the significant effect of the subject, it was conducted this research, supported by the acquisition of language theorists that establishes interfaces with the Lacan assumption s, such as Charles Melman, Christine Revuz and Jean-Claude Milner. Thus it was sought, in the speech of seven selected participants, after conducting a questionnaire and a semi-structured interview, evidences that could point out to the consequences from this bond with their mother tongue, understood as a barrier to the learning process of the French language, to this sampleinvestigated. From the outcome it was tried to understand what could be this linkage that those French foreign students faced in such a specific way, with their native spoken language, named by Revuz (2007) as founder language . For the analyses, it was chosen semi-structured interviews, as it is believed that allows us to be ahead of the process and that each participant is able to express their feelings related to their difficulties. It was given attention to their speeches, seeking for elements that could bring evidences of their faced barriers, such as repeated words, deviations of speech and intonation given to certain words. Additionally for analysis purposes, it was used some of the concepts proposed by Authier-Revuz, such as mismatches and discursive heterogeneity.The results put in evidence elements that are below our expectations and we believe that they will be useful to all that are involved with the acquisition process of foreign languages, especially students that faces similar situation as in the proportion that - without the objective of interpret these reflections and establish a diagnosis we can suggest then to reflect on their unique experience with their founder language and about the complexity of being involved and captured for some foreign language.